Reversible Unilateral Abducens Nerve Palsy in a patient with Scrub Typhus - A Clinical Diagnostic Dilemma: A Clinical Diagnostic Dilemma. - Choudhary, Rahul; Katoch, Gaurav; Sachdeva, Garima; Kushwah, Sweta (Journal of Nepal Paediatric Society, 2020)
Scrub typhus is an acute febrile rickettsial disease caused by Orientia tsutsugamushi. It infects endothelial cells and causes vasculitis, the predominant clinico-pathological feature of the disease. This results in disseminated inflammatory perivascular lesions leading to damage to the blood vessels affecting multiple end organs. Abducens nerve palsy is a known but extremely rare and reversible complication of scrub typhus. We present a case of scrub typhus with sixth cranial nerve involvement which responded to treatment with doxycycline.